A Retrospective Test-Negative Case-Control Study to Evaluate Influenza Vaccine Effectiveness in Preventing Influenza Among Immunocompromised Adults With a Solid Organ Transplant - Manon L. M. Prins; Manon L. M. Prins; Ernst D. van Dokkum; Ernst D. van Dokkum; Aiko P. J. de Vries; Maarten E. Tushuizen; Danny van der Helm; Edwin M. Spithoven; Irene M. van der Meer; J.H. Marc Groeneveld; Leo G. Visser; Saskia le Cessie; et al. (Transplant International)
Vaccination may prevent influenza in solid organ transplant (SOT) recipients. This study evaluates the influenza vaccine effectiveness (VE) in this high-risk population in the Netherlands. We also compared disease progression and 30-day mortality between vaccinated and unvaccinated influenza patients. In this multicenter, test-negative case-control study, SOT recipients with respiratory symptoms were included when tested for viral respiratory infections during the respiratory seasons between 1 January 2013 and 1 July 2024. Cases had a positive influenza PCR, while controls tested negative. Influenza vaccination in cases (74/174) and controls (291/602) were compared after adjusting for potential confounders. VE was calculated as (1-adjusted odds ratio) x 100. The overall VE was 6.9% (95% CI −40.9 to 38.4), with considerable variation across seasons. For those aged ≥65 years, VE was higher (32.4%, 95% CI −56.5–70.8) compared to those aged 18–64 years (4.8%, 95% CI −56.5 to 42.1). The adjusted VE against influenza A [7.5% (−46.0 to 41.3)] was higher than against influenza B (−3.8% (−146.7 to 56.3)). No differences in influenza-related complications were observed between the vaccinated and unvaccinated cases. The observed seasonal influenza vaccine effectiveness in adult SOT recipients is limited; further investigation for improvement is warranted.